The study of platelet indices in acute coronary syndromes - Manchanda, Jaya; Potekar, R M; Badiger, Sharan; Tiwari, Abhishek (Annals of Pathology and Laboratory Medicine, 2015)
Background: Platelets have been implicated in the pathogenesis of cardiovascular disorders including atherosclerosis and its complications such as acute myocardial infarction (MI), unstable angina and sudden cardiac death. Platelet indices correlates with functional status of platelets and is an emerging risk marker for atherothrombosis Methods: A prospective hospital based study was carried out on 175 cases diagnosed with Acute Coronary Syndromes and 175 controls from October 2011 to March 2013 considering the inclusion and exclusion criteria. Results: The incidence of ACS in males (62.86%) was more as compared to females (37.14%).The average age with which the patient presented with ACS was 57.76 Â± 13.19 years. The commonest manifestation of ACS was ST elevation MI. Analysis of PVI indicated MPV & PDW as significant risk factor for developing a myocardial infarction. This was in concordance with the elevated cardiac enzymes levels. Conclusion: The study concludes that Platelet Indices especially MPV & PDW is raised in patients who have suffered STEMI & NSTEMI as compared with patients diagnosed with unstable angina.